Collaborative Governance Berbasis Transformasi Digital Melalui Program Taring Dukcapil Di Disdukcapil Kota Denpasar - Wismayanti, Kadek Wiwin Dwi (Socio-political Communication and Policy Review, 2024)
The aim of this research is to find out how collaborative governance is based on digital transformation through the Taring Dukcapil program at the Denpasar City Disdukcapil. This research is qualitative research with descriptive approach. Research data was obtained through interview techniques, observation, questionnaires, documentation, and literature study. The Head of the Data Utilization and Service Innovation Division of the Denpasar City Disdukcapil, The Young Expert Policy Analysis of the Denpasar City Disdukcapil, and the people of Denpasar City were the informants for this research. The results of this research show four indicators in Collaborative Governance based on digital transformation through the Taring Dukcapil program in the Denpasar City Disdukcapil, namely: 1) Initial conditions, namely the conditions behind the formation of the Taring Dukcapil program in the Denpasar City Disdukcapil along with its supporting resources. 2) Institutional design, namely the existence of regulations or mechanisms to realize collaboration. 3) Leadership, namely the Taring Dukcapil program which is an initiative of the leadership of the Denpasar City Disdukcapil. 4) Collaborative process, namely face-to-face dialogue between the Denpasar City Disdukcapil and PT. Gojek and Grab finally reached an agreement to collaborate. To maintain the existing collaboration, each party makes a cooperation agreement which is expected to support sustainable collaboration. Abstrak Tujuan penelitian ini adalah untuk mengetahui bagaimana collaborative governance berbasis transformasi digital melalui program Taring Dukcapil di Disdukcapil Kota Denpasar. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Data penelitian diperoleh melalui teknik wawancara, observasi, kuesioner, dokumentasi, dan studi kepustakaan. Kepala Bidang Pemanfaatan Data dan Inovasi Pelayanan Disdukcapil Kota Denpasar, Analisis Kebijakan Ahli Muda Disdukcapil Kota Denpasar, dan masyarakat Kota Denpasar merupakan informan penelitian ini. Hasil penelitian ini menunjukkan empat indikator dalam collaborative governance berbasis transformasi digital melalui program Taring Dukcapil di Disdukcapil Kota Denpasar, yaitu: 1) Kondisi awal, yaitu keadaan yang melatarbelakangi dibentuknya program Taring Dukcapil di Disdukcapil Kota Denpasar beserta sumber daya pendukungnya. 2) Desain kelembagaan, yaitu adanya regulasi atau mekanisme dalam menjalin kolaborasi. 3) Kepemimpinan, yaitu adanya program Taring Dukcapil merupakan prakarsa dari pimpinan Disdukcapil Kota Denpasar. 4) Proses kolaboratif, yaitu adanya dialog tatap muka antara Disdukcapil Kota Denpasar dengan PT. Gojek dan Grab sampai akhirnya mencapai kesepakatan untuk melakukan kolaborasi. Untuk menjaga kolaborasi yang telah terjalin, masing-masing pihak membuat perjanjian kerja sama yang diharapkan dapat mendukung terjadinya kolaborasi yang berkelanjutan. Kata Kunci: Collaborative Governance; Administrasi Kependudukan; Taring Dukcapil